Composts Produced From Pig Slurry Solids: Nutrient Efficiency and N-Leaching Risks in Amended Soils - Santos, André; Fangueiro, David; Moral, Raul; Bernal, Maria Pilar (Frontiers in Sustainable Food Systems, 2018)
Composts were prepared from the solid fraction of pig slurry (SPS) by mixing with cotton gin waste (CGW) in two different proportions. The aim was to assess the fertilizer value of the two composts and to evaluate potential pollution risks due to the heavy metal (Cu and Zn) concentrations in the composts and the nitrate leaching following their soil application. For this, a pot trial using Italian ryegrass (Lolium multiflorum Lam.) as a test plant was run in a glasshouse. Two composts, A and B, prepared with SPS:CGW ratios of 4:3 and 3:4 (v:v), respectively (OM 63 and 57 %, TN 36.1 and 32.7, and TP 15.3 and 10.8 g kg-1 in A and B, respectively), were applied to a sandy loam soil at two doses based on the N supplied (D1: 360 mg TN pot-1, equivalent to 52 kg N ha-1, and D2: 720 mg TN pot-1). They were compared with a soluble mineral fertilizer (3.62 g pot-1 of N:P:K 10:10:10; providing 360 mg N pot-1); unfertilized control soil was also tested. The potential risk of nitrate-N leaching in the soil after two simulated intense rainfall events was evaluated. The experiment was carried out in double-layer pots, which allowed the collection of leachates. Both composts were able to increase plant biomass production and soil TN and available-P with respect to the control; available Cu and Zn in the soil did not increase significantly with respect to the control soil and mineral fertilizer treatment, although N deficiency limited plant growth at harvests 2 and 3. The compost prepared with a higher proportion of SPS (A) was more efficient for N fertilization (relative agronomic efficiency: 38.1-47.6 %; nitrogen use efficiency: 34.1-41.9 % of TN), due to its greater inorganic-N concentration. To obtain high P and K efficiencies application rates based on compost TN are recommended, which also prevent Cu and Zn soil enrichment. Nitrate leaching was very low in all treatments (<0.5 % of TN applied). Therefore, both composts can be used as organic fertilizers in the partial substitution of mineral fertilizers, without a significant nitrate leaching risk.